Ответ:
Пошаговое объяснение:
log₇(x-1)*log₇x=log₇x
ОДЗ
система
x-1>0
x>0
⇒ x>1
log₇(x-1)*log₇x-log₇x=0
log₇x(log₇(x-1)-1)=0
1) log₇x ; x=1 ∉ ОДЗ
2) log₇(x-1)-1=0
log₇(x-1)=1
log₇(x-1)=log₇7
x-1=7
x=8
проверка
log₇(8-1)*log₇8=log₇(8-1)*log₇8=log₇7*log₇8=log₇8
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
log₇(x-1)*log₇x=log₇x
ОДЗ
система
x-1>0
x>0
⇒ x>1
log₇(x-1)*log₇x-log₇x=0
log₇x(log₇(x-1)-1)=0
1) log₇x ; x=1 ∉ ОДЗ
2) log₇(x-1)-1=0
log₇(x-1)=1
log₇(x-1)=log₇7
x-1=7
x=8
проверка
log₇(8-1)*log₇8=log₇(8-1)*log₇8=log₇7*log₇8=log₇8